Analisis Kesulitan Pembelajaran Kalkulus Vektor Pada Satu Kelompok Mahasiswa - Nayara Sabila Lubis; Rani Selviani; Suci Dahlya Narpila (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
This study explores the difficulties experienced by a group of university students in learning vector calculus, particularly in understanding line integrals, surface integrals, and parametric forms. These challenges stem from a weak grasp of fundamental concepts, the abstract nature of the material, and a lack of supporting visual media. The research was conducted using a qualitative approach through interviews and observations of the student group. Results indicate that students struggle to apply vector integral concepts in problem-solving, especially in connecting theory with visual representation. The proposed solution involves the use of interactive visual-based learning methods and the gradual reinforcement of prerequisite materials.